2016
DOI: 10.1186/s12930-016-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

Low carbohydrate diet-based intervention for obstructive sleep apnea and primary hypothyroidism in an obese Japanese man

Abstract: BackgroundObesity is a major risk factor for obstructive sleep apnea (OSA), and weight loss is necessary in the overall management of obese patients with OSA. However, primary care physicians can provide only limited weight loss with lifestyle interventions, usually reducing a patient’s body weight by only 2.5 kg or less after 6–18 months.Case presentationA 45-year-old Japanese man was referred to our clinic owing to obesity, daytime sleepiness, and snoring during sleep. His weight was 130.7 kg and his body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A case‐report study in an obese Japanese man with obstructive sleep apnea revealed that weight was improved as well as lipid and glucose levels through following an LCD program. The authors have suggested that LCD helps to improve the management of patients with obstructive sleep apnea . LCD can improve endothelial function and inflammatory status, which is an important mechanism to manage mental health and cardiovascular diseases …”
Section: Discussionmentioning
confidence: 99%
“…A case‐report study in an obese Japanese man with obstructive sleep apnea revealed that weight was improved as well as lipid and glucose levels through following an LCD program. The authors have suggested that LCD helps to improve the management of patients with obstructive sleep apnea . LCD can improve endothelial function and inflammatory status, which is an important mechanism to manage mental health and cardiovascular diseases …”
Section: Discussionmentioning
confidence: 99%
“…8 A cross-sectional study in Greece revealed that OSA patients with the highest quartile of total red meat intake were three times more likely to have severe OSA than those with the lowest quartile. 9 Consistently, several epidemiological studies found that low-energy diet, low carbohydrate diet, and Mediterranean diet were associated with a decreased risk of OSA severity, [10][11][12][13][14][15] while the intake of red meat, unprocessed red meat, and proarteriosclerotic diet (high in calories, fat, and simple carbohydrates and low in fish, fresh fruits, and vegetables) could contribute to OSA severity. 9,16 Although some evidence supported the protective effect of certain healthy dietary elements in treating OSA, only one study 17 examined the association between dietary factors and sleep apnea risk.…”
Section: Introductionmentioning
confidence: 80%